Identified Seaweed Compound Diphenylmethane Serves as an Efflux Pump Inhibitor in Drug-Resistant Escherichia coli - Wen-Jung Lu; Pang-Hung Hsu; Chun-Ju Chang; Cheng-Kuan Su; Yan-Jyun Huang; Hsuan-Ju Lin; Margaret Lai; Gui-Xia Ooi; Jing-Yi Dai; Hong-Ting Victor Lin (MDPI AG, 2021)
Drug efflux pumps are one of the major elements used by antibiotic-resistant bacteria. Efflux pump inhibitors (EPIs) are potential therapeutic agents for adjunctive therapy, which can restore the activity of antibiotics that are no longer effective against pathogens. This study evaluated the seaweed compound diphenylmethane (DPM) for its EPI activity. The IC50 and modulation results showed that DPM has no antibacterial activity but can potentiate the activity of antibiotics against drug-resistant E. coli. Time-kill studies reported that a combination of DPM and erythromycin exhibited greater inhibitory activity against drug-resistant Escherichia coli. Dye accumulation and dye efflux studies using Hoechst 33342 and ethidium bromide showed that the addition of DPM significantly increased dye accumulation and reduced dye efflux in drug-resistant E. coli, suggesting its interference with dye translocation by an efflux pump. Using MALDI-TOF, it was observed that the addition of DPM could continuously reduce antibiotic efflux in drug-resistant E. coli. Additionally, DPM did not seem to damage the E. coli membranes, and the cell toxicity test showed that it features mild human-cell toxicity. In conclusion, these findings showed that DPM could serve as a potential EPI for drug-resistant E. coli.